análisis y evaluación a los estados financieros de Hoover Bermeo e hijos cía. ltda.., de la ciudad de cariamanga, período 2013-2014 - Montoya Apolo, Katty Carolina (2016)
Analysis and Evaluation Financial statements Hoover Bermeo e Hijos Cía. Ltda., allowed determination of the economic and financial structure of the entity with which the operating capacity available to the company in generating income and financial stability was evident. To comply fully with the first target for analysis and financial evaluation of the Company proceeded to implement the various financial indicators Financial Statements of the entity, so that fully met the economic and financial structure. Secondly we proceeded to assess its Financial Structure, Working Capital Conversion Cycle Cash, Dupont, EVA and Balance Point to evaluate each of the accounts included in these methods and see if they have an acceptable level in the financial management of the company. Finally, to the latest estimate compliance objective for research, and as a result of the analysis and financial evaluation made should Bermeo and Sons Co. Hoover. Ltda., The report revealing the economic and financial position in which the company is because it contains recommendations for the most important points in the opinion of the author benefit both the administrative and financial work was developed, what impact greater user demand, by virtue of the quality of the services they offer.